Assessing weight perception accuracy to promote weight loss among U.S. female adolescents: A secondary analysis - Yost Jennifer; Krainovich-Miller Barbara; Budin Wendy; Norman Robert (BMC, 2010)
Abstract Background Overweight and obesity have become a global epidemic. The prevalence of overweight and obesity among U.S. adolescents has almost tripled in the last 30 years. Results from recent systematic reviews demonstrate that no single, particular intervention or strategy successfully assists overweight or obese adolescents in losing weight. An understanding of factors that influence healthy weight-loss behaviors among overweight and obese female adolescents promotes effective, multi-component weight-loss interventions. There is limited evidence demonstrating associations between demographic variables, body-mass index, and weight perception among female adolescents trying to lose weight. There is also a lack of previous studies examining the association of the accuracy of female adolescents' weight perception with their efforts to lose weight. This study, therefore, examined the associations of body-mass index, weight perception, and weight-perception accuracy with trying to lose weight and engaging in exercise as a weight-loss method among a representative sample of U.S. female adolescents. Methods A nonexperimental, descriptive, comparative secondary analysis design was conducted using data from Wave II (1996) of the National Longitudinal Study of Adolescent Health (Add Health). Data representative of U.S. female adolescents (N = 2216) were analyzed using STATA statistical software. Descriptive statistics and survey weight logistic regression were performed to determine if demographic and independent (body-mass index, weight perception, and weight perception accuracy) variables were associated with trying to lose weight and engaging in exercise as a weight-loss method. Results Age, Black or African American race, body-mass index, weight perception, and weight perceptions accuracy were consistently associated with the likeliness of trying to lose weight among U.S. female adolescents. Age, body-mass index, weight perception, and weight-perception accuracy were positively associated (p < 0.05) with trying to lose weight. Black/African American subjects were significantly less likely than their White counterparts to be trying to lose weight. There was no association between demographic or independent variables and engaging in exercise as a weight-loss method. Conclusions Findings suggest that factors influencing weight-loss efforts, including age, race, body-mass index, weight perception, and weight-perception accuracy, should be incorporated into existing or new multi-component weight-loss interventions for U.S. adolescent females in order to help reduce the national epidemic of overweight and obesity among U.S. female adolescents.